Egg consumption, overall diet quality, and risk of type 2 diabetes and coronary heart disease: A pooling project of US prospective cohorts. Issue 5 (May 2021) - Djoussé, Luc; Zhou, Guohai; McClelland, Robyn.L.; Ma, Nanxun; Zhou, Xia; Kabagambe, Edmond. K.; Talegawkar, Sameera.A.; Judd, Suzanne. E.; Biggs, Mary. L.; Fitzpatrick, Annette.L.; Clark, Cheryl. R.; Gagnon, David. R.; et al.
Summary: Background and aims: Data on the relation of egg consumption with risk of type 2 diabetes (T2D) and coronary heart disease (CHD) are limited and inconsistent. Few studies have controlled for overall dietary patterns in egg-T2D or egg-CHD analyses, and it is unclear whether any observed elevated risks of T2D and CHD with frequent egg consumption is real or due to confounding by dietary habits. We tested the hypothesis that frequent egg consumption is associated with a higher risk of T2D and CHD risk after adjustment for overall dietary patterns among adults. Design: We used prospective cohort design to complete time-to-event analyses. Methods: We pooled de novo, harmonized, individual-level analyses from nine US cohorts (n = 103, 811). Cox regression was used to estimate hazard ratios separately in each cohort adjusting for age, ethnicity, body mass index (BMI), exercise, smoking, alcohol intake, and dietary patterns. We pooled cohort-specific results using an inverse-variance weighted method to estimate summary relative risks. Results: Median age ranged from 25 to 72 years. Median egg consumption was 1 egg per week in most of the cohorts. While egg consumption up to one per week was not associated with T2D risk, consumption of ≥2 eggs per week was associated with elevated risk [27% elevated risk of T2D comparing 7+ eggs/week with none (95% CI: 16%–37%)]. There was little evidence for heterogeneity across cohorts and we observed similar conclusions when stratified by BMI. Overall, egg consumption was not associated with the risk of CHD. However, in a sensitivity analysis, there was a 30% higher risk of CHD (95% CI: 3%–56%) restricted to older adults consuming 5–6 eggs/week. Conclusions: Our data showed an elevated risk of T2D with egg consumption of ≥2 eggs per week but not with <2 eggs/week. While there was no overall association of egg consumption with CHD risk, the elevated CHD observed with consumption of 5–6 eggs/week in older cohorts merits further investigation.